2006
DOI: 10.1111/j.1365-2125.2006.02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nelfinavir in HIV‐1‐infected pregnant and nonpregnant women

Abstract: AimsTo compare steady-state nelfinavir (NFV) pharmacokinetics in pregnant and nonpregnant HIV-infected women. MethodsTwenty-five pregnant HIV-infected women were selected from an ongoing observational study evaluating the pharmacokinetics of antiretroviral agents during pregnancy. Twenty of them were in the third and five in the second trimester. Data for the control group of 21 HIV-infected nonpregnant women were taken from a previous multicentre pharmacokinetic trial. All the participating women achieved ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…Significant decreases in the area under the concentration-time curve from 0 h to time (time between dosing intervals) have been demonstrated for ZDV (59), TNF (8), LPV (50), and NFV (7,43,56), while decreased trough concentrations have been noted for TNF (8), LPV (50), and NFV (55,56). ARV blood plasma concentrations observed in the present study were similar to those described in previous reports (8,23,36,38,50,56,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant decreases in the area under the concentration-time curve from 0 h to time (time between dosing intervals) have been demonstrated for ZDV (59), TNF (8), LPV (50), and NFV (7,43,56), while decreased trough concentrations have been noted for TNF (8), LPV (50), and NFV (55,56). ARV blood plasma concentrations observed in the present study were similar to those described in previous reports (8,23,36,38,50,56,59).…”
Section: Discussionmentioning
confidence: 99%
“…Paired maternal and cord blood plasma samples were obtained a median of 15.5 hours (range, 11.7 to 54.7) after the last dose. Table 2 summarizes drug concentrations in maternal blood plasma, cord blood plasma, and amniotic fluid and corresponding (17,33,56). N, number of paired BP and GT samples by period (second trimester, third trimester, postpartum, and nonpregnant historical controls, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is accompanied by a variety of physiological changes that affect pharmacokinetics [6], resulting in lower plasma concentrations for several protease inhibitors (PI) [7][8][9][10]. NVP is metabolized through the cytochrome P450 isoenzymes CYP 3A4 (56%) and CYP 2B6 (32%) [11].…”
mentioning
confidence: 99%
“…Within-subject comparisons between pregnancy and postpartum showed significant postpartum increases in maximum concentration and AUC, and decreases in oral clearance and the ratio of its active metabolite to the parent drug concentration [66,67]. Two recent studies of 25 and 27 pregnant women taking nelfinavir 1250 mg twice daily showed significantly lower troughs, peaks and AUC and higher oral clearance in the third trimester compared with the same women 6-12 weeks postpartum [68 • ] or nonpregnant controls [69]. Doses of 750 mg three times daily should be avoided in pregnancy.…”
Section: Nelfinavirmentioning
confidence: 99%